Imprisonment as A Subsidiary of Additional Penalty of Money Substitute for Corruption Crime: A Utility Perspective - Henderina Malo; H Hartiwiningsih; S Sulistyanta (Universitas Muhammadiyah Surakarta, 2025)
This normative legal research is conducted with the aim of analyzing the rules of imprisonment as a subsidiarity of additional compensation payments in the Corruption Crime Law which reflects the purpose of law as legal expediency. The research method used with several approaches, namely: legislative approach, conceptual approach and case approach. The results of this study found a number of problems regarding the provisions of imprisonment as a substitute for payment of restitution both at the level of the norm itself and in the implementation stage of the norm. In addition, the regulation of imprisonment as a substitute for restitution does not provide benefits as in Bentham's utilitarianism view. For the researchers, the regulation of imprisonment as a substitute payment does not pay attention to two important principles of the legislative process, namely the principle of proportionality and the principle of subsidiarity. The use of imprisonment as a substitute for additional payment of restitution is not effective in restoring state financial losses as expected by the legislator. This condition causes the legal provision to deviate from the purpose of law as legal benefit.